Inclusive Japanese Language Use In Support Of Gender Equality - Satriatama, Prasetya Eghy (Vocational College of Diponegoro University, 2024)
Gender-differentiated language use in Japanese stems from traditions and social norms that have developed over time. However, usage of gender-neutral Japanese is still not very popular in Japan. This article aims to provide an insight into gendered language use, particularly gender-based language use. The method used to write this article is a qualitative approach with an analytical descriptive method. The data is then collected through literature study. Also, the data sources used in this study are books, journals, articles and online news related to the uses of neutral Japanese in Japanese society. In this article, the author analyzes the data obtained from the book